Age differences in negative and positive expectancy bias in comorbid depression and anxiety. Issue 8 (17th November 2018) - Tadic, Dusanka; MacLeod, Colin; Cabeleira, Cindy M.; Wuthrich, Viviana M.; Rapee, Ronald M.; Bucks, Romola S.
ABSTRACT: Anxious individuals report disproportionately negative expectations concerning the future, termed the negative expectancy bias. In contrast, ageing is associated with an inflated expectancy for positive future events. A recent study [Steinman, S. A., Smyth, F. L., Bucks, R. S., MacLeod, C., & Teachman, B. A. (2013). Anxiety-linked expectancy bias across the adult lifespan. Cognition and Emotion, 27, 345–355. doi:10.1080/02699931.2012.711743 ] found using an interpretation bias task, a negative expectancy bias in young adults and positive expectancy bias in older adults with high trait anxiety. Extending this, the current study examined expectancy bias for positive, negative and ambiguously emotionally toned information in younger and older adults with clinical levels of depression and anxiety to community control groups, thus allowing examination of both disorder status and age on biases. Clinical participants reported a pervasive tendency to expect negative events relative to positive regardless of whether the current scenarios were positive, negative or ambiguous. Older adults showed greater expectancy for future positive scenarios when the initial scenario was negative or ambiguous. Age moderated the negative expectancy bias shown by clinical participants for ambiguous scenarios. Clinical disorders in older adults attenuated the positive expectancy bias that was otherwise strong in community participants. These findings provide further evidence for age differences in processing of emotionally toned information, with older adults showing a greater expectancy for positive future events.